STRATEGI KEMENTERIAN EKONOMI, PERDAGANGAN DAN INDUSTRI JEPANG DALAM MEMPERKUAT SOFT POWER DAN MENINGKATKAN PENDAPATAN INDUSTRI KREATIF MELALUI KEBIJAKAN COOL JAPAN/CREATIVE INDUSTRIES TAHUN 2010-2016 - Widyatomo, Nicko Retnanto (Global and Policy Journal of International Relations, 2017)
ABSTRACTUntil 2010 Japan's popular culture is still a popular culture product, but post-2010 popularity of Japanese popular culture products began to decline. Facing this situation Japan's Ministry of Economy, Trade and Industry (METI) initiated Japan to popularize Japan's popular culture and increase the revenue of Japan's creative industries that produce popular culture contents through the Cool Japan/Creative Industry policy. This policy aims to promote Japanese popular culture content with the theme of Cool Japan abroad and also to increase the revenue of Japanese creative industries. With the formulation of this policy is expected to become an alternative source of declining Japanese national income. METI will then conduct cultural diplomacy as a strategy of this policy in several countries including the United States, France and Singapore by holding cultural events in these countries as a means of promoting and influencing the interest of overseas consumers.Keywords: METI, Cool Japan/Creative Industry, Popular Culture, Cultural DiplomacyDOI: https://doi.org/10.33005/jgp.v5i01.1903